Lactiplantibacillus plantarum AR113 Exhibit Accelerated Liver Regeneration by Regulating Gut Microbiota and Plasma Glycerophospholipid - Xie, Chunliang; Zhang, Zhoumei; Yang, Manyi; Cao, Cha; Zhou, Yingjun; Zhu, Zuohua; Gong, Wenbing; Xu, Chao; Yan, Li; Hu, Zhenxiu; Ai, Lianzhong; Peng, Yuande (Frontiers in Microbiology, 2022)
Emerging evidence indicates that probiotics have been proved to influence liver injury and regeneration. In present study, the effects of Lactobacillus plantarum AR113 on the liver regeneration were investigated in 70% partial hepatectomy (PHx) rats. Sprague-Dawley(SD) rats were gavaged with L. plantarum AR113 suspensions (1×1010 CFU) both before or after partial hepatectomy. The results showed that L. plantarum AR113 administration two weeks before partial hepatectomy can accelerate liver regeneration by increased hepatocyte proliferation and tumor necrosis factor-α(TNF-α), hepatocyte growth factor(HGF) and transforming growth factor-β(TGF-β) expression. Probiotic adminstration enriched Lactobacillus and Bacteroides and depleted Flavonifractor and Acetatifactor in the gut microbiome. Meanwhile, L. plantarum AR113 showed decline of phosphatidyl ethanolamine (PE), phosphatidylcholine (PC), phosphatidyl serine (PS), and lysophosphatidyl choline (LysoPC) levels in the serum of the rats after the L. plantarum AR113 administration. Moreover, L. plantarum AR113 treated rats exhibited higher concentrations of L-leucine, L-isoleucine, mevalonic acid and lower 7-oxo-8-amino-nonanoic acid in plasma than that in PH rats. Spearman correlation analysis revealed a significant correlation between changes in gut microbiota composition and glycerophospholipid. These results indicate that L. plantarum AR113 is promising for accelerating liver regeneration and provide new insights regarding the correlations among the microbiome, the metabolome and liver regeneration.